Lewis Acid Catalyzed Synthesis of Cyclic Carbonates, Precursors of 1, 2‐ and 1, 3‐Diols. Issue 23 (11th July 2014) - Cornil, Johan; Gonnard, Laurine; Guérinot, Amandine; Reymond, Sébastien; Cossy, Janine
Abstract: An eco‐friendly synthesis of cyclic carbonates through a Lewis acid catalyzed cyclization of tert ‐butyl carbonates is described. These cyclic carbonates are precursors of 1, 2‐ and 1, 3‐diols, and the developed method was applied to a short synthesis of a diarylheptanoid, (3 S, 5 S )‐alpinikatin. Abstract : FeCl3 · 6H2 O and InCl3 are able to catalyze the cyclization of allylic and homoallylic tert ‐butyl carbonates into their cyclic counterparts, which are direct precursors of 1, 2‐ and 1, 3‐diols. The method was used as the key step in a short synthesis of an aryl heptanoid natural product (3 S, 5 S )‐alpinikatin.